Gas tungsten arc welding of NiTi shape memory alloy - Barbosa, David José Pintão dos Santos Fontes (2014)
Shape memory alloys are characterized by the ability of recovering their initial shape after being deformed and by superelasticity. Since the discovery of these alloys, a new field of interest emerged not only for the scientific community but also to many industries. However, these alloys present poor machinability which constitute a constrain in the design of complex components for new applications. Thus, the demand for joining techniques able to join these alloys without compromising their properties became of great importance to enlarge the complexity of existing applications. Literature shows that these alloys are joined mainly using laser welding. In the present study, similar NiTi butt joints, were produced using TIG welding. The welds were performed in 1.5 mm thick plates across the rolling direction. A special fixture and gas assist device was designed and manufactured. Also a robot arm was adapted to accommodate the welding torch to assure the repeatability of the welding parameters. Welds were successfully achieved without macroscopic defects, such as pores and distortions. Very superficial oxidation was seen on the top surface due to insufficient shielding gas flow on the weld face. The welded joints were mechanically tested and structurally characterized. Testing methods were used to evaluate macro and microstructure, as well as the phase transformation temperatures, the mechanical single and cyclic behaviour and the shape recovery ability. Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), microhardness measurements were techniques also used to evaluate the welded joints. A depletion in Ni in the fusion zone was seen, as well as a shift in Ms temperature. For strain values of 4% the accumulated irrecoverable strain was of about 30% and increased with the strain imposed during cycling. Nevertheless, a complete recovery of initial shape was observed when testing the shape memory effect on a dedicated device that introduces a deformation of 6.7%. That is, the welding procedure does not remove the ability of the specimens to recover their initial shape.